Temperature and vibration thresholds in vibration syndrome. - Ekenvall, L (1986)
In a study to investigate whether the quantitative assessment of temperature and vibration thresholds can improve the evaluation of the neurological symptoms in vibration syndrome 37 patients with neurological symptoms (paraesthesias, numbness, pain) in the hands who had worked with hand held vibrating tools and 46 healthy controls not exposed to vibration were examined. Temperature thresholds were measured on the thenar eminence and on the volar side of the second and third fingers held together. Vibration thresholds were determined on the dorsum of the hand and on the dorsal side of the second and fifth fingers proximal to the nail. The neutral zone between thresholds for warmth and cold was much wider in the patients than in the controls. Patients older than 45 had higher vibration thresholds than controls. Electroneurography was abnormal in 18 of 34 patients and a carpal tunnel syndrome was diagnosed in six subjects. This investigation is thus indicated in patients with neurological symptoms. Seven of the patients with normal electroneurographic findings had impaired temperature or vibration thresholds or both. Determination of sensory thresholds seems to add valuable information and the methods are, by contrast with electroneurography, easily adapted to the screening of exposed groups outside hospital. Our results indicate that thin myelinated and unmyelinated nerve fibres might be damaged in the vibration syndrome.